Avaliação da assistência pré-natal na rede básica do município de Maringá-Paraná - Bauli, Janaina Daiane (2009)
Changes in the Unified Health System (SUS) and the existence of consolidated programs, with the requirement to meet criteria, enable the evaluation practice of services rendered and the health of their users. From the existing programs, the prenatal care is worth mentioning because it is a focus on traditional in the UBS. . It is believed that by identifying strengths and difficulties in their development will be possible to make inferences about other activities in the Basic Health Units (UBS). This study aimed at evaluating the prenatal care in primary care in Maringá; knowing the profile of those mothers who used prenatal service in the UBS; verifying the physical resources used in the care of pregnant women; identifying the professionals working in prenatal care; observing whether the minimum procedures recommended by the Birth and Prenatal Humanization Program (PHPN) are being followed; and verifying the record quality of the assistance given. The literature review, showed that research on maternal health is expanding, but most of the publications used only secondary data. Similar to a study carried out in 1994, the sample consisted of 115 mothers admitted to a charity hospital, accredited to the SUS for deliveries. After the interviews, which used a structured instrument on prenatal care, we visited the twenty-two UBS (88%) where the mothers reported having their prenatal care assistance. The work process, the physical structure, and the use of the Family Health Strategy (ESF) in prenatal care were observed and the quality of medical records was analyzed. Comparison with similar indicators to the previous study and the adapted Kessner index were used to analyze the data, which combined the essential criteria in prenatal care to verify the adequacy of care. The results, showed no significant increase in the number of health facilities in the city and that there are units with inadequate physical infrastructure for the service. However, there was an increase in the number of professionals working in the public health network. The criteria established by the service program is met only partially and the medical records are still undervalued, with no relevant information. When applied the Kessner index for both the perception of mothers as to the records prenatal performed only appropriate when analyzing the number of consultations and the start of monitoring. However, assistance was considered inadequate when the other criteria needed were combined. It was found that the prenatal care and other programs of primary care can be improved. Greater involvement of professionals with prenatal care is needed, especially by members of the ESF and by the male nurse, who must use the tools of this strategy to emphasize their work process and the provision of care to pregnant women. Investment in assessment practices should become regular in the health services in order to enhance the training process and improve decision making in services.